Leader Humility and Machiavellianism: Investigating the Effects on Followers’ Self-Interested and Prosocial Behaviors - Chen, Shu-Chen; Zou, Wen-Qian; Liu, Na-Ting (Frontiers in Psychology, 2022)
Existing research on leader humility primarily demonstrates its positive effects. This study challenges this view by proposing the potential negative effects of leader humility on followers’ behaviors. Furthermore, this paper employs the person-situation interactionist perspective to extend the research on integrating followers’ personality traits and leader humility. Specifically, this study proposed that leader humility triggers their followers’ sense of power; moreover, this study wagers that whether followers’ sense of power encourages self-interested or prosocial behavior in followers depends on their particular Machiavellian traits. The theoretical model was tested using the time-lagged supervisor–subordinate matched data obtained. Our findings revealed that follower Machiavellianism fosters the relationship between a sense of power and self-interested behavior but it weakens the relationship between a sense of power and prosocial behavior. Thus, this study provides a better understanding regarding the effect of follower personality and leader humility on follower behavioral reactions.